2022
DOI: 10.3389/fvets.2022.852240
|View full text |Cite
|
Sign up to set email alerts
|

Productive Performance and Blood Biochemical Parameters of Dairy Cows Fed Different Levels of High-Protein Concentrate

Abstract: This study investigated the productive traits and some blood biochemical parameters of high-yielding Ayrshire dairy cows fed at different levels of Agro-Matic@LLC NGO, Russia (Agro-Matic (AM)) protein concentrate. A total of 45 high-yielding Ayrshire cows were selected and divided into three groups, each 15. The control group (0AM) fed the basal ration, while group two (1AM) and group three (2AM) fed a basal ration by replacing sunflower cake with different levels of AM (1 and 1.5 kg/head/day), respectively. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In our early works devoted to the use of a new protein feed protein concentrate Agro-Matic (PCAM), which is made from poultry meat processing waste and crushed white lupine grain in feeding lactating cows [31][32][33][34][35], it was shown that the inclusion of it in various quantities in the diet of highly productive Ayrshire dairy cows showed a positive effect on milk productivity and milk quality throughout the lactation period, improved digestibility of nutrients, nitrogen retention in the body without deterioration of the physiological and the sanitary condition of cows. Moreover, the inclusion of 1.5 kg/head/day PCAM was the best regarding economic benefits [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our early works devoted to the use of a new protein feed protein concentrate Agro-Matic (PCAM), which is made from poultry meat processing waste and crushed white lupine grain in feeding lactating cows [31][32][33][34][35], it was shown that the inclusion of it in various quantities in the diet of highly productive Ayrshire dairy cows showed a positive effect on milk productivity and milk quality throughout the lactation period, improved digestibility of nutrients, nitrogen retention in the body without deterioration of the physiological and the sanitary condition of cows. Moreover, the inclusion of 1.5 kg/head/day PCAM was the best regarding economic benefits [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a microbiota with antimicrobial activity that stimulates animal immunity, such as Bifidobacterium sp. and Bacillus sp., has been elevated [32,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The symbiotic microflora of the rumen perform a detoxification function, participate in the digestibility of nutrients, prevent the invasion of parasites and pathogens and stimulate the development of immunity [ 4 , 5 , 6 ]. Therefore, the maintenance and functioning of the microbiota are also important factors in the prevention of gastrointestinal diseases, such as lactate acidosis, alkalosis, ketoses, laminates, mastitis and limb diseases, which significantly increase the productivity of dairy cattle [ 2 , 3 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%